2023
DOI: 10.1007/s00262-023-03466-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and prognostic factors of PD-1 inhibitors combined with lenvatinib and Gemox chemotherapy as first-line treatment in advanced intrahepatic cholangiocarcinoma: a multicenter real-world study

Abstract: Background A programmed cell death protein-1 (PD-1) inhibitor combined with lenvatinib and Gemox chemotherapy as first-line therapy demonstrated high anti-tumor activity against biliary tract cancer in phase II clinical trials. Herein, we aimed to investigate the efficacy and safety for advanced intrahepatic cholangiocarcinoma (ICC) in a multicenter real-world study. Methods Patients with advanced ICC who received PD-1 inhibitor combined with lenvatinib an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Notably, one patient receiving sintilimab discontinued treatment due to severe bone marrow suppression (grade 4). According to a multicenter study that included 53 patients, researchers reported that all patients experienced irAEs (30). Fatigue, both in any grade and grade 3 or higher, was the most common adverse event, with 41.5% of patients experiencing severe (grade 3 or higher) reactions, and one case of grade 4 bone marrow suppression, findings similar to those of our study.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, one patient receiving sintilimab discontinued treatment due to severe bone marrow suppression (grade 4). According to a multicenter study that included 53 patients, researchers reported that all patients experienced irAEs (30). Fatigue, both in any grade and grade 3 or higher, was the most common adverse event, with 41.5% of patients experiencing severe (grade 3 or higher) reactions, and one case of grade 4 bone marrow suppression, findings similar to those of our study.…”
Section: Discussionsupporting
confidence: 89%
“…(B) CA19-9 levels before and after chemotherapy. 11.6) months, respectively (33). These results suggest that the combination of ICIs with chemotherapy and TKIs is another promising approach for the treatment of ICC, which will be investigated in future clinical studies.…”
Section: Discussionmentioning
confidence: 72%
“…Zhu et al. investigated the efficacy of PD-1 inhibitors combined with TKI lenvatinib and GEMOX chemotherapy as first-line treatment in advanced ICC, and reported a median OS and progression-free survival of 14.3 (95% CI: 11.3–not reached) and 8.63 (95% CI: 7.17–11.6) months, respectively ( 33 ). These results suggest that the combination of ICIs with chemotherapy and TKIs is another promising approach for the treatment of ICC, which will be investigated in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy may not only up-regulate checkpoint expression and alter immune cell infiltration, it also works by disrupting strategies used by tumors to evade immune recognition. The results of several clinical trials and real-world studies suggest that the addition of targeted therapies to immune-combination chemotherapy is a promising approach for the treatment of BTC, but is also challenged by the high incidence of adverse effects ( 1 4 ). Wang et al.…”
mentioning
confidence: 99%
“…Chemotherapy may not only up-regulate checkpoint expression and alter immune cell infiltration, it also works by disrupting strategies used by tumors to evade immune recognition. The results of several clinical trials and real-world studies suggest that the addition of targeted therapies to immune-combination chemotherapy is a promising approach for the treatment of BTC, but is also challenged by the high incidence of adverse effects (1)(2)(3)(4). Wang et al reported a case of progressive ICC with poor results of first-line chemotherapy, which was treated with ICI plus tyrosine kinase inhibitor combined with radiotherapy in the second line to achieve better efficacy.…”
mentioning
confidence: 99%